Tri Hita Karana: A Holistic Framework for Sustainable Tourism Development in Bali - Yuhan, Wang; Widiastini, Ni Made Ary (Badan Riset dan Inovasi Daerah Provinsi Bali, 2026)
Purpose: This study aimed to analyze the role of Tri Hita Karana as a governance framework in sustainable tourism development in Bali and to evaluate the implementation of its three pillars in destination practices. Research methods: This research applied a qualitative descriptive approach with a case study design. Data were collected through field observation and literature review. Informants were selected using purposive sampling. Data were analyzed using thematic analysis and source triangulation. Results and discussion: Tri Hita Karana functioned as an operational framework for strengthening community participation, environmental conservation, and cultural preservation. Effective implementation was found in community-based destinations but faced environmental, social, and governance challenges. Implication: Institutional integration of Tri Hita Karana within regional regulation and destination.